CLASSIFICATION OF FACTORS FOR INCREASING THE INVESTMENT ACTIVITY OF SMALL INDUSTRIAL ZONES - Mannopova Shaxnoza Elshodovna (American Journals Publishing, 2023)
The article examines the processes associated with the strategic opportunities and conditions for increasing the investment activity of small industrial zones. Theoretical and methodological factors influencing the process of ensuring investment activity in small industrial zones have been studied. The directions and opportunities for overcoming the factors that negatively affect the investment activity of small industrial zones are based. Scientific proposals and practical recommendations on the formation of strategic directions for increasing the investment activity of small industrial zones in Uzbekistan.
Keywords: small industrial zones, investment program, investment project, investment activity, investment policy, investment potential, investment environment, investment resource.